Diversity analyses of bacterial symbionts in four Sclerodermus (Hymenoptera: Bethylidae) parasitic wasps, the dominant biological control agents of wood-boring beetles in China - Kang, Kui; Wang, Lina; Gong, Jun; Tang, Yanlong; Wei, Ke (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveSclerodermus wasps are important biocontrol agents of a class of wood borers. Bacterial symbionts influence the ecology and biology of their hosts in a variety of ways, including the formation of life-long beneficial or detrimental parasitic infections. However, only a few studies have explored the species and content of the symbionts in the Sclerodermus species.MethodsHere, a high-throughput sequencing study of the V3-V4 region of the 16S ribosomal RNA gene revealed a high level of microbial variety in four Sclerodermus waps, and their diversities and functions were also predictedResultsThe three most prevalent phyla of microorganisms in the sample were Firmicutes, Bacteroides, and Proteus. The KEEG pathways prediction results indicated that the three pathways with the highest relative abundances in the S. sichuanensis species were translation, membrane transport, and nucleotide metabolism. These pathways differed from those observed in S. guani, S. pupariae, and S. alternatusi, which exhibited carbohydrate metabolism, membrane transport, and amino acid metabolism, respectively. Bacteroides were found to be abundant in several species, whereas Wolbachia was the most abundant among S. sichuanensis, with a significant negative correlation between temperature and carriage rate.ConclusionsThese results offer insights into the microbial communities associated with the bethylid wasps, which is crucial for understanding how to increase the reproductive capacity of wasps, enhance their parasitic effects, and lower cost in biocontrol.